Changing Dynamics in Geopolitics: Implications for Taiwan
IX, 194 p. 5 illus., 2 illus. in color.
Keywords: This edited volume explores Taiwan's future through focused analyses of geopolitical security challenges in the Indo-Pacific region. Against the backdrop of China's increasing threats, international scholars examine evolving geopolitical dynamics and their implications for world order stability. The book presents diverse perspectives from Europe, the UK, the US, and Asia-Pacific across three sections: changing geopolitical dynamics, Cross-Strait warfare including legal and gray-zone tactics, and China-US competition. Chun-Yi Lee, Associate Professor at the School of Politics and International Relations and Director of the Taiwan Research Hub, University of Nottingham. Simona Grano, Head of the research area China-Taiwan relations and Director of the Taiwan Studies Project at the University of Zurich, Research Fellow at the European Research Center on Contemporary Taiwan (ERCCT) Tübingen, and Research Associate at SOAS London.